Regional Trade Agreements Versus Broad Liberalization : Which Path Leads to Faster Growth? Time-Series Evidence - Vamvakidis, Athanasios (IMF Working Papers; Working Paper, 1998)
Should a closed economy open its trade to all countries or limit itself to participation in regional trade agreements (RTAs)? Based on time-series evidence for a data set for 1950-92, this paper estimates and compares the growth performance of countries that liberalized broadly and those that joined an RTA. The comparisons show that economies grew faster after broad liberalization, both in the short and long run, but slower after participation in an RTA. Economies also had higher investment shares after broad liberalization, but lower ones after joining an RTA. The policy implications support broad liberalization.